Enhancing Service Quality of Islamic Savings Products: A Strategy to Improve Customer Interest in SAHARA BMT NU East Java - Rudi Ruskiyanto; Razali Razali; Ahmad Majdi Tsabit (Asian Journal of Law and Islamic Finance, 2025)
This study explores the enhancement of service quality for Islamic savings products at BMT NU East Java, specifically focusing on the SAHARA (Savings for Hajj and Umrah Arrangements) product designed to facilitate religious pilgrimages. Using qualitative field research conducted from January to April 2024, the study examines current service quality dimensions and their impact on customer interest. Findings reveal that BMT NU East Java employs three primary service approaches: "jemput bola" (staff visiting customers), office service, and online channels. The institution enhances service quality through transparency, personalized attention, and religious alignment, while growing customer interest through community networks and trust-building. Despite fluctuating customer numbers over 2016-2021, significant growth was observed in 2021 despite pandemic challenges. The research suggests that integrating traditional service quality dimensions with religious considerations is essential for Islamic financial institutions serving pilgrimage-focused savings products. Strategic recommendations include balancing digital innovation with personal service, strengthening community engagement, and maintaining Shariah compliance while improving operational efficiency.